Modeling temperature dynamic effects for high‐power light‐emitting diodes - Kyatam, Shusmitha (2022)
Temperature is a dynamic variable in most electronic devices. As the device operates, it generates heat, which translates in a temperature increase. Available models commonly disregard these variations due to the fact that they manifest at very large time scales. However, temperature dynamic effects have profound implications on the device model and on our common understanding. This paper discusses implications of considering the temperature variations on the current–voltage characteristic curves of power light-emitting diodes. The main theoretical results establish that the current equation has a memristive nature when temperature is assumed as a dynamical state variable. This hypothesis is then validated experimentally.